Dynamic nanoindentation testing for studying thermally activated processes from single to nanocrystalline metals. Issue 6 (December 2015) - Durst, Karsten; Maier, Verena
Highlights: Overview on advances in dynamic indentation testing for studying thermally activated processes in metals and alloys. Background on thermally activated deformation mechanism in metals and how pyramidal indentation testing can be used for measuring local mechanical properties and thermally activated processes. New nanoindentation strain rate jump tests as well as nanoindentation long term creep test. Examples and applications of the measurement procedures are given for face-centered cubic (fcc) and body-centered cubic (bcc) metals and alloys with special emphasis on the influence of the material microstructure in terms of single crystalline (sx), ultrafine grained (ufg), and nanocrystalline (nc) grain structure. Possible issues with comparing hardness test results to uniaxial testing and introduce the concept of a steady state hardness creep test. Abstract: Nanoindentation experiments are widely used for assessing the local mechanical properties of materials. In recent years some new exciting developments have been performed for also analyzing thermally activated processes using indentation based techniques. This paper focuses on how thermally activated dislocation mechanisms can be assessed by indentation strain rate jump as well as creep testing. Therefore, a small overview is given on thermally activated dislocation mechanism and how indentation data from pointed indenters can be interpreted in terms of uniaxial macroscopic testing. This requires the use of the indentation strain rate as introduced by Lucas and Oliver as well as the concepts of Taylor hardening together with Johnson expanding cavity model. These concepts are then translated to nanoindentation strain rate jump tests as well as nanoindentation long term creep test, where the control of the indenter tip movement as well as the determination of the contact are quite important for reliable data. It is furthermore discussed, that for a steady state hardness test, the interpretation of the hardness data is straightforward and comparable to macroscopic testing. For other conditions where size effects play a major role, hardness data need to be interpreted with consideration for the microstructural length scale with respect to the contact radius. Finally strain rate jump testing and long term creep testings are used to assess different thermally activated mechanisms in single to nanocrystalline metals such as: Motion of dislocation kink pairs in bcc sx-W, Grain boundary processes in nc-Ni and ufg-Al, and the Portevin-le Chatelier effect in ufg-AA6014.